A content analysis of the book Biology for the Space Age (Philippine edition) textbook and laboratory manual workbook - Bonus, Elmyra A.; Gamboa, Luviminda O.; Manuel, Alberto J. (1975)
This paper establishes the Student Involvement and Word Loading Profiles of the Philippine edition of Bro. Charles' Biology for the Space Age through content analysis. It aimed to determine whether the books are authoritarian or inquiry-oriented and to examine the indices of student involvement as could be derived from the analysis of the: textual prose; figures, diagrams, tables; end of chapter questions; and activities.